2000
DOI: 10.1128/jb.182.23.6707-6713.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combination of Different −10 Hexamers and Downstream Sequences on Stationary-Phase-Specific Sigma Factor ς S -Dependent Transcription in Pseudomonas putida

Abstract: The main sigma factor activating gene expression, necessary in stationary phase and under stress conditions, is S . In contrast to other minor sigma factors, RNA polymerase holoenzyme containing S (E S ) recognizes a number of promoters which are also recognized by that containing 70 (E 70 ). We have previously shown that transposon Tn4652 can activate silent genes in starving Pseudomonas putida cells by creating fusion promoters during transposition. The sequence of the fusion promoters is similar to the 70 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…Then, the overexpression cassette of P. putida fis was cloned into pJB785TT (Santos et al, 2001). The luc gene in pJB785TT was replaced with the 2 kb BamHI-XbaI fragment from pBR-lacItac (Ojangu et al, 2000) carrying a lacI q -P tac cassette to obtain pJB-lacI q -P tac . Then, the fis gene (PP4821) was amplified from the chromosomal DNA of P. putida PaW85 by PCR using oligonucleotides fisRBSPstI (59-CACTGCAGAAGGGGTGGCCGCA-TGAC-39) and fisBamHI (59-ATGGATCCTTACAACAAGTCGTAC-TGC-39).…”
Section: Methodsmentioning
confidence: 99%
“…Then, the overexpression cassette of P. putida fis was cloned into pJB785TT (Santos et al, 2001). The luc gene in pJB785TT was replaced with the 2 kb BamHI-XbaI fragment from pBR-lacItac (Ojangu et al, 2000) carrying a lacI q -P tac cassette to obtain pJB-lacI q -P tac . Then, the fis gene (PP4821) was amplified from the chromosomal DNA of P. putida PaW85 by PCR using oligonucleotides fisRBSPstI (59-CACTGCAGAAGGGGTGGCCGCA-TGAC-39) and fisBamHI (59-ATGGATCCTTACAACAAGTCGTAC-TGC-39).…”
Section: Methodsmentioning
confidence: 99%
“…The pheBA promoter resembles the catBCA promoter and is also activated by CatR (Kasak et al, 1993 ;Parsek et al, 1995). Comparative studies of the interaction of CatR with the promoters of the pheBA and catBCA operons have revealed that the CatRmediated activation mechanism is well conserved, despite the different origins of these operons (Parsek et al, 1995 ;Tover et al, 2000).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Subsequently, the catBCA promoter was inserted using BamHI-and XhoI-generated ends into the promoter-probe vector pKTlacZ to obtain plasmid pZ-catBCA. For the construction of P. putida CatR overexpression strain PaWCatR + , the catR gene was cloned from plasmid pKR∆HF (Rothmel et al, 1991) by using HindIII-and EcoRI-generated ends to the vector pBRlacItac (Ojangu et al, 2000) cleaved with same enzymes (pBRlacItaccatR in Table 1). The CatR expression cassette lacI q -Ptac-catR was inserted into pUC18Not using EcoRI-and BamHI-generated ends.…”
Section: Cloning Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to construct a control strain expressing the luxAB genes under the control of the P tac promoter, the BamHI-generated DNA fragment containing the lacI q -P tac regulatory region was subcloned from pBRlacItac (Ojangu et al, 2000) into plasmid pUCNotluxAB to obtain plasmid pUCNottacluxAB. Then, the lacI q -P tac -luxAB expression cassette was inserted into the NotI site of plasmid mTn5SSgusA40.…”
mentioning
confidence: 99%